1996
DOI: 10.1007/bf00041405
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed mutagenesis of the CP 47 protein of photosystem II: alteration of conserved charged residues which lie within lethal deletions of the large extrinsic loop E

Abstract: The intrinsic chlorophyll-protein CP 47 is a component of photosystem II which functions in both light-harvesting and oxygen evolution. The large extrinsic loop E of this protein has been shown to interact with the oxygen-evolving site. Previously, Vermaas and coworkers have produced a number of deletions within loop E which yielded mutants which were unable to grow photoautotrophically and which could not evolve oxygen at normal rates. During the course of our site-directed mutagenesis program in Synechocysti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Sukenik et al (43) have shown that 1/ WC is correlated with carboxylation in the Calvin cycle rather than electron transport reactions within the thylakoid membranes. A similar discrepancy between photoautotrophic growth and photosynthetic efficiency has been observed in certain cyanobacterial mutants altering the CP47 polypeptide of PSII (44).…”
Section: Discussionsupporting
confidence: 70%
“…Sukenik et al (43) have shown that 1/ WC is correlated with carboxylation in the Calvin cycle rather than electron transport reactions within the thylakoid membranes. A similar discrepancy between photoautotrophic growth and photosynthetic efficiency has been observed in certain cyanobacterial mutants altering the CP47 polypeptide of PSII (44).…”
Section: Discussionsupporting
confidence: 70%
“…In addition, protein structural database indicate that deletion mutations are also involved in protein sequence evolution in nature [11], suggesting that deletion mutations can be included in the mutagenesis step of directed evolution. Despite these potentials of deletion mutagenesis in protein sequence engineering and evolution, the approach has not been popularly used compared to substitution mutagenesis method because deletions lead to relatively large structural perturbations, and so the target proteins are prone to be inactivated [12], [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…The Glu364 to Gln substitution affects PS II electron transfer processes, due to an effect on Y D Previous studies of loop E in CP47 identified amino acid residues that are now known to be located adjacent to Y D [3,4,16] that were important for PS II assembly and function [19,45]. Among these a Glu364 to Gln substitution in CP47 appeared to produce only a minor phenotype, but the inability of an E364Q:ΔPsbV double mutant to grow photoautotrophically indicated the importance of this residue [20,21]. Although the Glu364 to Gln substitution did not substantially affect growth and oxygen evolution in the earlier studies, this study has unmasked potentially deleterious changes in PS II electron transfer processes in the E364Q strain, which we attribute to alterations in the H-bonding network around Y D (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the cyanobacterium Synechocystis sp. PCC 6803 (hereafter Synechocystis 6803), CP47 Glu364 to Gln or Glu364 to Gly substitutions produced strains similar to the wild‐type, in contrast to severely impaired growth in a Phe363 to Arg mutant . Loop E of CP47 extends into the thylakoid lumen and is involved in binding of the cyanobacterial PS II extrinsic subunit PsbO, which, along with the PsbU, PsbV, and possibly CyanoQ proteins, protects the OEC and Y D from the reductive environment of the lumen and is necessary for maximal rates of oxygen evolution .…”
mentioning
confidence: 99%